Grassroots Activism in the Belly of the Beast: A Relational Account of the Campaign Against Urban Fracking in Texas. (26th October 2017) - Auyero, Javier; Hernandez, Maricarmen; Stitt, Mary Ellen
Abstract: This article offers a relational account of the emergence, development, and impact of a social movement against urban fracking in Denton, Texas. It highlights the role played by the interactions between grassroots activism, local officials, and other stakeholders in the political construction of shared understandings of environmental risk. Drawing upon scholarship on risk perceptions and on social movement outcomes, the article argues that as a result of relationships of conflict and cooperation between activists, officials, residents, and oil and gas industry representatives, a field of opinion about the potential (negative) impacts of fracking emerged. It shows that grassroots, face-to-face, joint action played a key role in the campaign to ban fracking. Localized collective action should be at the front and center of social scientific examinations of shared understandings of environmental danger.